Arboreal arthropod assemblages in chili pepper with different mulches and pest managements in freshwater swamps of South Sumatra, Indonesia - Siti Herlinda; Titi Tricahyati; Chandra Irsan; Tili Karenina; Hasbi HASBI; Suparman SUPARMAN; Benyamin Lakitan; Erise Anggraini; Arsi arsi (Society for Indonesian Biodiversity, 2021)
Abstract. Herlinda S, Tricahyati T, Irsan C, Karenina T, Hasbi, Suparman, Lakitan B, Anggraini E, Arsi. 2021. Arboreal arthropod assemblages in chili pepper with different mulches and pest managements in freshwater swamps of South Sumatra, Indonesia. Biodiversitas 22: 3057-3066. In the center of freshwater swamps in South Sumatra, three different chili cultivation practices are generally found, namely differences in mulch and pest management that can affect arthropod assemblages. The effect of mulches and pest management on arboreal arthropod assemblages specific to chili production centers in the freshwater swamps of South Sumatra has never been investigated. This study aimed to observe arboreal arthropod assemblages in chili with different mulches and pest management. Arboreal arthropods were sampled using sweep nets in three locations with plots treated with leaf litter mulch and bioinsecticide, plastic mulch and synthetic insecticide, and weedy plot without mulch with synthetic insecticide. The species number of arboreal arthropods found was 28 species of Arachnids and 23 species of Insects, and consisting of 6 families of the Arachnids and 25 families of Insects. The abundance of arboreal arthropods was 65.60 individuals/5 nets per observation. In the chili field without mulch but with the insecticide, the species biodiversity and abundance of arboreal predatory arthropods were the highest. In contrast, in the chili field, that applied with synthetic insecticides and plastic mulch, the abundance of arboreal predatory arthropods was the lowest. The herbivorous insect populations in chili with plastic mulch and synthetic insecticides and the chili with the leaf litter mulch were higher than those in the chili without mulch. In the chili with the leaf litter mulch and bioinsecticide, the species number and abundance of the spiders were the highest compared to the other chili fields. The weedy chili field without mulch and chili with the leaf litter mulch has proved ideal habitats for the arboreal predatory arthropods.